Hating Empire Properly : The Two Indies and the Limits of Enlightenment Anticolonialism - Agnani, Sunil M. (Book collections on Project MUSE., 2013)
The author produces a novel attempt to think the eighteenth-century imagination of the West and East Indies together, arguing that this is how contemporary thinkers Edmund Burke and Denis Diderot actually viewed them. This concern with multiple geographical spaces is revealed to be a largely unacknowledged part of the matrix of Enlightenment thought in which eighteenth-century European and American self-conceptions evolved. By focusing on colonial spaces of the Enlightenment, especially India and Haiti, the author demonstrates how Burke's fearful view of the French Revolution - the defining event of modernity - as shaped by prior reflection on these other domains. Exploring with sympathy the angry outbursts against injustice in the writings of Diderot, the author nonetheless challenges recent understandings of him as a univocal critic of empire by showing the persistence of a fantasy of consensual colonialism in his thought. By looking at the impasses and limits in the thought of both radical and conservative writers, the author asks what it means to critique empire "properly."